THE ECCENTRIC DIGRAPH OF THE CORONA OF $Cn$ WITH $Km$, $Cm$ OR $Pm$ - Sri Kuntari; Tri Atmojo Kusmayadi (Journal of the Indonesian Mathematical Society, 2012)
pdf abstractDOI : http://dx.doi.org/10.22342/jims.18.2.117.113-118